Skala współczucia dla Innych(CS-R-PL) - Fopka-Kowalczyk, Małgorzata Joanna; Flakus, Maria; Kocur, Dagna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Objective: The project aimed to adapt to the Polish of the revised version of the Compassion Scale for Others created by Elisabeth Pommier, Kristin Neff, and Tóth-Király. Adaptation took place in two main stages: cultural and psychometric validation. Methods and materials: The research used the 2020 CS-R scale, a metric with selected demographic data, a NEO-FFI personality test, and the Self-Compassion Scale (SCS-PL). Participants: 645 adults living in these Polish participated in the study. Results: The data obtained in the process of adaptation and validation allow the introduction of the Compassion for Others Scale on the ground of Polish. CS-R-PL enables Polish practitioners and researchers to assess their skills in practicing compassion, for example, among specialists or people already professionally involved in helping, to plan and create appropriate training in this area.